Constitutional Originalism : A Debate - Bennett, Robert W. (Robert William), 1941- (Book collections on Project MUSE., 2011)
"Debates about constitutional originalism and its rival, living constitutionalism, are old. Originalists insist that the meaning of the United States Constitution is fixed. The words and phrases of the constitutional text have the same meaning today as they did when the Constitution was ratified by the requisite nine states in 1788 (or when each amendment was ratified). Living constitutionalists believe that the meaning of the Constitution must adapt to changes in values and circumstances. The two authors of the essays that follow clearly have different attitudes toward what is called originalism in constitutional interpretation. Lawrence Solum advocates a form of constitutional originalism; Robert Bennett's views align with a version of living constitutionalism. But the essays reveal that this contrast shrouds a host of complexities, both in the definitions of the concepts and in approaches to interpretation. Together the essays provide an introduction to the contemporary debates about the role of original understanding in constitutional interpretation"--Preface, p. [vii].